Vegetation diversity as a factor in carbon sequestration and storage: examples from the ultramafic forests in Palawan Island, Philippines - De Castro, Ma. Ellenita Gibe; Padrones, Jenielyn; Boco, Katrina (Brawijaya University, 2025)
A floristic study was conducted in two ultramafic formations in Palawan Island, selected for their differing land uses, to assess the role of ultramafic forests as a carbon sink based on plant diversity and Soil Organic Carbon (SOC) content. A total of 17 tree species were identified inside an active mining area in Mt. Bulanjao, Rio Tuba, Bataraza, while only 15 tree species in Magarwak, Brgy. Sta. Lourdes, Puerto Princesa City. Palawan Mangkono (Xanthostemon speciosus Merr.), an island endemic species that thrives well in ultramafics, is the most dominant species in Rio Tuba, Bataraza, whereas Putian (Mastixia pentandra Blume) is the dominant species in Puerto Princesa City based on the Important Value Index (IVI). In terms of diversity, both sites exhibited low diversity index values, with Bataraza site having H'=2.232 while Magarwak, Puerto Princesa City had H'=2.286, respectively. Such data implied the alarming rate of species lost in ultramafic forest, primarily attributable to anthropogenic activities. Further analysis of SOC content indicated that Puerto Princesa City's ultramafic soils contained 99.05 t ha-1, while a much lower value of 85.68 t ha-1 at Bataraza was quantified. Considering the combined contribution of vegetation diversity and soil carbon, this study suggests that Puerto Princesa City's ultramafic formations have the potential to sequester atmospheric carbon and may act as a sink. Both the unusual characteristics of ultramafic soils and their existing vegetation contribute to the enhancement of the carbon storage potential of this forest type, although present land use serves as a crucial consideration. These findings underscore the importance of preserving and conserving native metallophytes in the area, making this research a pivotal basis for conservation efforts.